Padimedical: Medical Image Sharing Portal with DICOM Viewer – User Experience - Tharek, A.; Muda, Ahmad Sobri; Basseri Huddin, Azzam; Abdul Rahim, Ezamin; Ann Git, Kim; Ahmad Sabri, Muhammad Izzat; Abdullah, Ruzi (International Journal of Human and Technology Interaction (IJHaTI), 2020)
Digital Imaging and Communication in Medicine (DICOM) is a standard medical imaging format for medical imaging information and data. Availability to access DICOM files remotely using smartphones has shown to improve healthcare systems especially for communication between doctors fromdifferent centres. Most of DICOM files need to be viewed using conventional institutional DICOM viewer. We developed software which allows medical personnel to access DICOM images remotely from their smartphone. This newly created software platform is named Padimedical. This pilot study aims to evaluate users’ satisfaction and usability. Practising medical doctors from a radiology department in a tertiary referral centre were chosen as correspondents in this study. The survey form was sent to over 30 doctors via email. A total of 24 out of 30 respondents completed the survey. The survey showed that Padimedical DICOM viewer was easily accessible (100%), compatible with OS operating system (100%), user-friendly (87.1%), and high signal to noise ratio (100%). All respondents (100%) agreed that the image viewing was smooth and responsive. All respondents would recommend to their peers (n=24). A total of 18 respondents suggested that the quality of images was high (76%) and 23 respondents suggested that the contents in this newly created platform were easy to share (96.15%). All the participants were able to make the correct diagnosis using Padimedical. Overall, the rating of our platform is 4.3 out of 5. Conclusion: Based on this pilot survey, Padimedical software was easily accessible remotely using smartphones, compatible with OS operating system, viewing images were smooth and responsive, produce high-quality image, and easy to share DICOM contents. Keywords—DICOM, images, software